The Use Of Word Coinage In Students’ Daily Conversation - Faiqah Mahmudah (IJER (Indonesian Journal of Educational Research), 2017)
Abstract This research discusses about an analysis of word. In linguistics, study of word is analysed under morphology. To specify the research, this research focuseson the use of word coinage in daily conversation of third semester students of English study program. The aims of this research to describe and find out some words of word coinage that used by the students in their daily conversation. This research uses descriptive qualitative method. There are three kinds of word coinage that explained in this research; Invention, blend and clipping. Invention is word processes that create a word by adapting a name of commercial product. Blend is a merge or combine two words become a new word. And Clipping is create a new word by shorter the original word. Key words: linguistics, morphology, word coinage